About the need for optical gear measurements using a beam diversion mechanism in order to obtain truthful surface texture parameters / Beurteilung der Notwendigkeit einer Strahlumlenkung für optische Zahnradmessungen zur Bestimmung korrekter Oberflächentexturkennwerte - Müller, Andreas; Hausotte, Tino (Technisches Messen)
The following article shows, that the optical characterisation of work piece surfaces with varying angles of inclination leads to different surface texture parameters. These results justify the development of a customised measurement setup using a optical beam diversion mechanism for the correct evaluation of gear wheel flank
Keywords: Surface texture parameters; focus variation; angle of incidence; gear wheel measurement

Analysis of the random measurement error of areal 3D coordinate measurements exclusively based on measurement repetitions - Müller, Andreas; Hausotte, Tino (Technisches Messen, 2021)
The measurement uncertainty characteristics of a measurement system are an important parameter when evaluating the suitability of a certain measurement system for a specific measurement task. The measurement uncertainty can be calculated from observed measurement errors, which consist of both systematic and random components. While the unfavourable influence of systematic components can be compensated by calibration, random components are inherently not correctable. There are various measurement principles which are affected by different measurement error characteristics depending on specific properties of the measurement task, e. g. the optical surface properties of the measurement object when using fringe projection or the material properties when using industrial X-ray computed tomography. Thus, it can be helpful in certain scenarios if the spatial distribution of the acquisition quality as well as uncertainty characteristics on the captured surface of a certain measurement task can be found out. This article demonstrates a methodology to determine the random measurement error solely from a series of measurement repetitions without the need of additional information, e. g. a reference measurement or the nominal geometry of the examined part.<br
Keywords: Measurement uncertainty; 3D coordinate measurement; single point uncertainty; industrial X-ray computed tomography

Assessment of the single point uncertainty of dimensional CT measurements - Fleßner, Matthias; Müller, Andreas; Götz, Daniela; Helmecke, Eric; Hausotte, Tino (NDT.net issue Vol.21 No.02, 2016)
A method analysing the local variations of a series of CT measurements to determine the single point noise is presented. Using a realistic simulation model of the CT system, the mean local offset and the single point uncertainty can additionally be estimated. The method is tested on a measurement series of a micropart. It is shown that the method is capable of identifying areas of increased uncertainty caused by artefacts and of quantifying the value of the single point uncertainty. Additionally, the method is validated using an existing method that is capable of assessing the local quality of a CT measuremen
Keywords: computed tomography; dimensional metrology; single point noise; systematic offset; single point uncertainty; uncertainty mapping; error sources; simulation; artefacts

Automated detection of artefacts for computed tomography in dimensional metrology - Fleßner, Matthias; Müller, Andreas; Helmecke, Eric; Hausotte, Tino (Digital Industrial Radiology and Computed Tomography, 2015)
Artefacts within CT volume data have a large impact on the results of dimensional measurements. To avoid measurement deviations, it is therefore crucial to identify regions affected by artefacts. The presented method analyses the volume data in the proximity of an extracted surface point to calculate a Local Quality Value (LQV). Using this method, surface points affected by artefacts are identified and highlighted in 2D and 3D visualisations. As only the volume data and the extracted surface are required to calculate the LQV, no additional knowledge like a CAD model or a reference measurement is necessary and the analysis can be carried out automatically. CT scans of calibrated gauges blocks that exhibit large errors in the segmented surface dataset due to artefacts are used to demonstrate the capability of the presented method. It is shown that it is possible to increase the accuracy of dimensional measurements by considering the information provided by the LQV.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.lfmt.automa
Keywords: dimensional metrology; computed tomography; artefacts; surface point quality; surface point uncertainty

Automated evaluation of the surface point quality in dimensional X-ray computed tomography - Müller, Andreas; Butzhammer, Lorenz; Wohlgemuth, Florian; Hausotte, Tino (Technisches Messen, 2020)
X-ray computed tomography (CT) enables dimensional measurements of numerous measurands with a single scan, including the measurement of inner structures. However, measurement artefacts complicate the applicability of the technology in some cases. This paper presents a methodology to assess the surface point quality of computed tomography measurements without the requirement of a CAD model. Measurement artefacts lowering the surface point quality can therefore automatically be detected. The correlation of quality values with the random measurement error is demonstrated. The presented method can in principle be used to weight single fit points to reduce the measurement uncertainty of CT measurement
Keywords: Industrial X-ray computed tomography; surface point quality; volume data; segmentation

Bestimmung und Berücksichtigung der Einzelpunktmessunsicherheit in virtuellen Toleranzanalysen - Heling, Björn; Müller, Andreas; Schleich, Benjamin; Hausotte, Tino; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 4. Summer School - September 2020, 2020)

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas; Hausotte, Tino (Measurement Science & Technology, 2022)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (360^° rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.<br

Characterization of the single point precision of steel gear wheel measurements using tactile coordinate measurement machines in scanning mode - Müller, Andreas; Metzner, Sebastian; Hausotte, Tino (20. GMA/ITG-Fachtagung Sensoren und Messsysteme 2019, 2019)
The framework of the single point uncertainty developed at the Institute of Manufacturing Metrology (FMT) presents a methodology to determine and evaluate the local measurement uncertainty for a measurement setup by local comparison of a measurement series with an associated reference geometry. This approach, which was originally developed and optimized for the processing of complete areal measurements of work pieces, was now also extended to line scans found in dimensional testing using tactile coordinate measurement machines (CMM). Target of the investigation are straight-toothed steel gear wheels, which can be dimensionally characterized by both helix and profile scans using a CMM in scanning mode in combination with a rotatory stage. The modification of the single point uncertainty framework in order to determine the single point precision of repeated gear wheel measurements was implemented successfully but the test setup also yielded abnormally high random measurement errors, which could not fully be explained within our examination
Keywords: gear wheel; tactile coordinate measurement; single point precision; scanning mode

Comparison of different measures for the single point uncertainty in industrial X-ray computed tomography - Müller, Andreas; Hausotte, Tino (9th Conference on Industrial Computed Tomography, 2019)
The concept of single point uncertainty describes a methodology to statistically evaluate the local measurement results of a measurement series with respect to the associated reference geometry. The single point uncertainties can be used as local quality parameters or weighting factors in subsequent processing of a measurement and can therefore have a significant impact on the final measurement results. The core routine used in former work at the Institute of Manufacturing Metrology, which is based on ray-triangle intersection tests, provided accurate results under most conditions. Nevertheless, some disadvantages were observed, including the very high computational demand and an inaccurate sampling of edge regions. In order to compensate for these deficiencies, another distance measure utilizing an expanded nearest neighbour approach was implemented and compared to the existing solution. It could be shown that the alternative solution for the determination of the single point uncertainty in repeated computed tomography (CT) measurements can provide very similar results while having substantially less computational requirements on the hardware used.<br
Keywords: dimensional metrology; single point uncertainty; ray tracing; GPGPU

Comparison of Geometrically Derived Quality Criteria regarding Optimal Workpiece Orientation for Computed Tomography Measurements - Butzhammer, Lorenz; Müller, Andreas; Hausotte, Tino (10th Conference on Industrial Computed Tomography, Wels, Austria (iCT 2020), 2020)
In the field of industrial Computed Tomography (CT), the orientation of the workpiece influences the local quality of the reconstructed volume data and therefore dimensional measurements. In the literature, different a priori criteria for an optimal orientation are proposed, which are purely based on the part and setup geometry. However, it is not evident to which extent they correlate with the measurement accuracy or how different quality parameters should be weighted, especially if a wider range of materials and therefore different artefact contributions should be covered. In this work, existing methods and criteria are compared and extended. In contrast to most existing investigations, different quality parameters are evaluated not only globally, but also restricted to relevant regions of interest (ROI). A straightforward derivation for an analytical determination of surface areas affected by cone-beam artefacts is presented. Results show that an ROI-based evaluation is important to find an optimal orientation for single measurands. The investigated quality parameter based on the prediction of surface areas which are affected by cone-beam artefacts was found to be applicable as exclusion criterion. This only holds true if the evaluation is restricted to relevant ROI surface areas, which should also be considered when evaluating the maximum X-ray penetration length as quality parameter. The correlation of the latter with resulting measurement deviations was found to depend on the measurement tas
Keywords: Computed Tomography; Workpiece Orientation; Cone-Beam Artefacts; Artefact Reduction; Optimisation; Dimensional Metrology

Consideration and impact assessment of measurement uncertainty in the context of tolerance analysis - Heling, Björn; Müller, Andreas; Schleich, Benjamin; Hausotte, Tino; Wartzack, Sandro (Proceedings of the ASME 2019 International Mechanical Engineering Congress and Exposition, 2019)

Data fusion of surface data sets of X-ray computed tomography measurements using locally determined surface quality values - Müller, Andreas; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2018)
X-ray computed tomography as a measurement system faces some difficulties concerning the quality of the acquired measurements due to energy-dependent interaction of polychromatic radiation with the examined object at hand. There are many different techniques to reduce the negative influences of these artefact phenomena, which is also the aim of this newly introduced method. The key idea is to create several measurements of the same object, which only differ in their orientation inside the ray path of the measurement system. These measurements are then processed to selectively correct faulty surface regions. To calculate the needed geometrical transformations between the different measurements with the goal of a congruent alignment in one coordinate system, an extension of the iterative closest point (ICP) algorithm is used. To quantitatively classify any surface point regarding its quality value to determine the individual need of correction for each point, the local quality value (LQV) method is used, which has been developed at the Institute of Manufacturing Metrology. Different data fusion algorithms are presented whose performances are tested and verified using nominal–actual comparison
Keywords: X-Ray Computed Tomography; Local Quality Values; Data Fusion

Determination of the single point precision associated with tactile gear measurements in scanning mode - Müller, Andreas; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2020)
The framework of the single point uncertainty developed at the Institute of Manufacturing Metrology (FMT) presents a methodology to determine and evaluate the local measurement uncertainty for a measurement setup by local comparison of a measurement series with an associated reference geometry. This approach, which was originally developed and optimized for the processing of complete areal measurements of work pieces using industrial X-ray computed tomography, was now also extended to line scans found in dimensional testing using tactile coordinate measuring machines (CMMs). The targets of the investigation are spur (involute) steel gear wheels, which can be dimensionally characterized by both helix and profile scans using a CMM in scanning mode in combination with a rotatory table. A second measurement procedure is characterized by a single scan of the complete gear profile without the usage of a rotatory table, using the “free-form scan” CMM functionality. The modification of the single point uncertainty framework in order to determine the single point precision of repeated gear wheel measurements was implemented successfully for gear measurements using the Zeiss Gear Pro evaluation software in combination with a rotatory table as well as unassisted free-form scans of the same gear. The examinations yielded abnormally high random measurement errors, which could not fully be explained within our examinations and was for the most part caused by the accuracy of the used rotatory table of the CMM. The alternative measurement method showed that the CMM system is capable of measuring very precisely in scanning mode if the changes in the curvature of the scan trajectory are favourabl
Keywords: single point uncertainty; measurement precision; tactile gear measurement

Determination of the single point uncertainty of customized polymer gear wheels using structured-light scanning with various polygonization settings - Müller, Andreas; Schubert, Dominik; Drummer, Dietmar; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2020)
During the manufacturing of work pieces, geometrical deviations from the intended nominal geometry of the designer are inevitable. The procedure of conformance testing defined in ISO 14253-1:2018-07 is used to ensure the function of a work piece by verifying the geometrical compliance with pre-defined tolerance specifications. Depending on the measurement setup used for the validation step, it is possible that the local measurement uncertainty is too large in order to provide a meaningful conformance evaluation. This paper aims to demonstrate the complete workflow of the determination of the locally defined single point uncertainty and its components (systematic and random measurement error, respectively) for a given measurement task. It was shown for an optical measurement setup in combination with an industrial X-ray computed tomography reference measurement system that different necessary colouring methods of polymer (POM) gear wheels, which are required to enable measurements using structured-light scanning, have a measurable influence on the local distribution of the measurement uncertainty. Because of the fact that the presented method is dependent on a discrete surface sampling, the effects of different polygonization settings during the creation of the areal measurement result were evaluated in order to rate the reduced data complexity against the hereby possibly increased measurement uncertainty. The gained information regarding the local measurement uncertainty of a measurement setup can then be used for downstream processes in various use cases, e.g. for the improvement of holistic tolerance simulation models or the improvement of geometrical measurements using weighted regression analysis. Additionally, the visualization of the areal distribution of the measurement uncertainty enables a powerful tool to optimize the used measurement setu
Keywords: single point uncertainty; structured-light scanning; polymer gear wheel

Development of a virtual metrological CT for numerical measurement uncertainty determination using aRTist 2 - Wohlgemuth, Florian; Müller, Andreas; Hausotte, Tino (Technisches Messen, 2018)
The development of a virtual metrological CT for numerical measurement uncertainty determination at the Institute of Manufacturing Metrology (FriedrichAlexander- University Erlangen-Nuremberg (FAU), Germany) using the software aRTist 2 by the BAM German Federal Institute for Materials Research and Testing is described. The virtual metrological CT uses a Monte-Carlo approach for numerical measurement uncertainty determination. Results demonstrating that numerical uncertainty determination according to GUM Supplement 1 and in accordance with uncertainty determination according to guideline VDI/VDE 2630 Part 2.1 is possible for selected measurement tasks are presented.
Keywords: X-ray computed tomography; Monte Carlo simulation; aRTist 2; metrology; measurement uncertainty

Einfluss des Bildrauschens innerhalb der Messkette eines industriellen Computertomografen - Propagation of image noise through the measurement chain in industrial X-ray computed tomography - Reuter, Tamara; Müller, Andreas; Hausotte, Tino (DGZfP-Jahrestagung 2022, 2022)

Evaluating and visualizing the quality of surface points determined from computed tomography volume data - Fleßner, Matthias; Müller, Andreas; Helmecke, Eric; Hausotte, Tino (PTB open access repository, 2015)
By evaluating the volume data in the proximity of a surface point, a Local Quality Value (LQV) is calculated for each surface point of a Computed Tomography (CT) measurement. This allows an automatic and reliable identification of areas containing surface points with reduced accuracy. A colour-coded visualisation of the LQV allows a highlighted display of untrustworthy measurement data. This method is capable of identifying a broad range of artefacts (including beam hardening, noise and rounded off edges) and of points of reduced accuracy due to the fixture of the part on the rotational stage.
UnivIS-Import:2015-04-17:Pub.2015.tech.FT.lfmt.evalua
Keywords: Dimensional metrology; computed tomography; artifacts; surface determination; surface point quality; surface point uncertainty

Evaluation of reflection properties of sheet bulk metal formed parts by pixel wise analysis of camera images provided for triangulation measurement - Metzner, Sebastian; Ramesh, Rahul; Müller, Andreas; Hausotte, Tino (ITG-Fachbericht 281 Sensoren und Messsysteme, 2018)
Dimensional measurements with optical measuring systems often involve challenges for reflective surfaces. Especially, measuring systems which use structured light for measurement generate overexposed regions in reflective areas of the workpiece. The present work describes a possibility to extend a point cloud, taken by a fringe projection system, with a quality value to provide information concerning the uncertainty of the measured points and the reflection properties of the surface. This quality value is based on a measurement of the workpiece with passive triangulation. This allows in addition a subsequent extension of the initial measurement with the fringe projection system with the point cloud of the passive triangulation.<br

Implementation of a beam hardening correction method for mono material parts using a linearization technique - Müller, Andreas; Butzhammer, Lorenz; Hausotte, Tino (International Symposium on Digital Industrial Radiology and Computed Tomography, 2019)
Common X-ray sources for industrial computed tomography (CT) exhibit a polychromatic spectrum. While the absorption of radiation by the measurement object is dependent on the X-ray energy, the commonly used reconstruction algorithms assume an absorption coefficient under monochromatic conditions. In the context of industrial CT, the material of a measurement object is oftentimes known, which makes the application of a linearizing beam hardening correction method possible for parts made out of a single material. In this work, we present an efficient setup and data processing pipeline to determine and manage experimental X-ray absorption models for mono material parts. This pipeline estimates the correlation between attenuation and penetration length using a cone shaped specimen and subsequently corrects the grey values of the projections of a measurement object of the same material as the specimen. In contrast to commonly used step wedges, the special specimen makes it possible to sample the absorption curve with a large number of grid points, while using a standard measurement operation mode for the CT system. The correction method makes it possible to measure the tooth flanks of a steel gear wheel, which could otherwise not be measured due to beam hardening artefacts

Implementation of Parameterized Work Piece Deviations and Measurement Uncertainties into Performant Meta-models for an Improved Tolerance Specification - Müller, Andreas; Oberleiter, Thomas; Willner, Kai; Hausotte, Tino (Proceedings of the Design Society: International Conference on Engineering Design, 2019)
Geometrical work piece deviations are unavoidable and directly affect the function and quality of technological products. Tolerance management is regarded as a crucial subtask of the development of technological products, because it ensures the function as well as a sufficient product quality while maintaining reasonable production costs. That means, that geometric tolerances as an essential part of the product description greatly affect the functional capability, manufacturability, mountability, verifiability and the costs of the final product. The research group FOR 2271 was founded to enable the computer-aided specification of tolerances, which meet the requirements of production, assembly, verification and function by close cooperation between the departments responsible for product design, assembly and metrology. The aim of this contribution is to determine the manufacturing process scatter as well as the measurement uncertainty and establish ways and means to include that information into efficient meta-models, ultimately enabling improved and accurate tolerance analyse
Keywords: Tolerance representation and management; Uncertainty; Product modelling / models

Improving geometry element regression analysis for dimensional X-ray computed tomography measurements using locally determined quality values - Müller, Andreas; Hausotte, Tino (10th Conference on Industrial Computed Tomography (iCT) 2020, 2020)
X-ray computed tomography (CT) enables the determination of numerous dimensional measurands with a single scan. However, measurements are often affected by artefacts, which are mainly caused by the effects of the complex physical interactions between the used radiation, the measurement object and the detector as well as the algorithms used for measurement data processing. Surface regions affected by artefacts lead to an inaccurate surface determination and therefore to increased measurement deviations and uncertainties of geometric measurements. This contribution aims to demonstrate the possibility of detecting negatively affected surface regions by a qualitative examination of the underlying volume data in the region of each determined surface point. This classification is used to improve different kinds of sphere measurements, which are evaluated by performing regression analysis onto the measured point clouds. Because of the available qualitative classification for each surface point, it is possible to apply a suitable weighting metric before applying the regression analysis in order to reduce the influence of lowly classified surface areas onto the measurement result. The workflow is demonstrated with a calibrated multi-sphere specimen. The results show that a significant reduction of the measurement errors associated with the evaluation of sphere centre distances, sphere form and radius deviations, respectively, can be achieved, while using the regression analysis tools of the commercial software VGStudio Max (Volume Graphics GmbH
Keywords: measurement uncertainty; dimensional metrology; regression analysis; local quality values

Improving template-based CT data evaluation by integrating CMM reference data into a CAD model-based high fidelity triangle mesh - Müller, Andreas; Hausotte, Tino (Nondestructive Testing and Evaluation, 2022)
Industrial X-ray computed tomography is a relatively recent technology in the field of 3D coordinate metrology. The available technical solutions represent capable systems, which are continuously adapted for different applications. Nonetheless, some profound limitations and technical challenges remain (e.g. effects of the polychromatic X-ray spectrum and a strong correlation between image quality and measurement duration), which require continuous efforts in order to improve the accuracy of such systems in the context of dimensional metrology. Therefore, this contribution demonstrates the integration of CMM measurement data into a CAD model in order to generate full reference measurements, which can be used to evaluate the measurement accuracy of CT systems. Currently, much effort is being made in order to improve simulations of CT systems with the goal to realistically recreate real CT measurements. In order to validate the simulation model by comparison against physical CT measurements, the geometry of the measurement object has to be known as accurately as possible. The presented approach shows how to generate geometries from CMM reference data which are suited to be used as an input for CT simulation tools. Detailed technical descriptions of the algorithms are given and demonstrated based on real measurements.<br
Keywords: Measurement uncertainty; dimensional CT; nominalactual comparison; triangle mesh; Voronoi interpolation

Methoden zur Reduzierung und Berücksichtigung der Unsicherheiten von dimensionellen Messgrößen in der Toleranzanalyse - Müller, Andreas; Heling, Björn; Schleich, Benjamin; Oberleiter, Thomas; Willner, Kai; Wartzack, Sandro; Hausotte, Tino (Industriekolloquium der Forschergruppe FOR 2271, 2019)

Separation of locally determined work piece deviations and measurement uncertainties for structured-light scanning of customized polymer gear wheels - Müller, Andreas; Metzner, Sebastian; Hausotte, Tino; Schubert, Dominik; Drummer, Dietmar (20. GMA/ITG-Fachtagung Sensoren und Messsysteme 2019, 2019)
During the manufacturing of work pieces, geometrical deviations from the intended nominal geometry of the designer are inevitable. The procedure of conformance testing defined in ISO 14253-1:2018-07 is used to ensure the function of a work piece by verifying the geometrical compliance with pre-defined tolerance specifications. Depending on the measurement setup used for the validation step and the accuracy of the manufacturing process, it is possible that the measurement uncertainty is large enough to have a significant influence on the conformance evaluation. The measurement uncertainty for optical measurement systems is influenced by the surface properties of the test specimen. This contribution aims to demonstrate the complete workflow for the determination of the single point uncertainties for a given measurement task in order to separate the local work piece deviations from the systematic and random components of the measurement uncertainty. It could be shown for a demonstration scenario that different necessary coloring methods of polymer gear wheels, which are required to enable measurements using structured-light scanning, have a measureable influence on the local distribution of the measurement uncertainty. This information could then be used for downstream processes in various use cases, e.g. for the improvement of holistic tolerance simulation models or the improvement of geometrical measurements using weighted regression analysi
Keywords: structured-light scanning; work piece deviations; measurement uncertainty; gear wheel; colored polymer

Simulation-based correction of systematic errors for CT measurements - Müller, Andreas; Wohlgemuth, Florian; Hausotte, Tino (8th Conference on Industrial Computed Tomography, 2018)
A large number of influencing quantities can induce measurement deviations for dimensional measurements using computed tomography. The article describes a newly developed simulation-based correction method for computed tomography coordinate measurements. Using a steel gauge block it is demonstrated that the method can significantly reduce the deviation of the measured surface from the real form of the measurement object. The computed tomography system used has a maximum acceleration voltage of 130 kV. Therefore, a steel gauge block is a relatively challenging measurement object due to the likely occurrence of beam hardening artefacts. The results show that, for a given computed tomography system, the described method can extend the range of objects for which dimensional measurements are feasibl
Keywords: X-ray computed tomography; simulation; artefacts; correction; systematic error; ray tracing

Spot size and detector unsharpness determination for numerical measurement uncertainty determination - Orgeldinger, Christian; Wohlgemuth, Florian; Müller, Andreas; Hausotte, Tino (9th Conference on Industrial Computed Tomography, 2019)
As the experimental measurement uncertainty evaluation for comp uted tomography is currently an expensive and time-consuming task, numerical uncertainty evaluation (according to GUM Supplement 1) using a virtual CT is a promising alternative. For this digital twin to simulate accurate measure ment results, the virtual CT system needs to be modelled as reallistically as possible using adequate input parameters for the simulation. This paper describes a method for the separateddetermination of two significant input parameters: focal spot size and detector unsharpness. The method is tested using a widerange of measurement parameters on a Zeiss Metrotom 1500 with different test specimen. It could be shown that the method yields reasonable results for most parameters. In addition, the re is a dependence of the focal spot size on the ratio of tube voltage and tube current at constant power. This contradicts the wide-spread rule of thumb that the spot size depends on the tube power only. Indications of a changing focal spot shape at high powers could be detecte
Keywords: ocal spot; detector unsharpness; numerical measurement uncertainty evaluation; virtual coordinate measuring machine; dimensional metrology

SURROGATE MODELING CONSIDERING MEASURING DATA AND THEIR MEASUREMENT UNCERTAINTY - Oberleiter, Thomas; Müller, Andreas; Hausotte, Tino; Willner, Kai (Uncecomp 2019 Proceedings, 2019)
Virtual approaches to manufacturing processes are a common tool in developing components today. Simulations are always containing uncertainties like simplifying assumptions in computer aided modelling, material deviations, fluctuating external loads or other known and unknown influences. To integrate such uncertainties in an early design stage, the input parameters should be defined as intervals, because insufficient data may be available at this stage to provide probability distributions. To consider such epistemic uncertainties, a large number of intervals can be merged into a fuzzy number. For each interval a membership value is assigned which depends on the interval limits and an expert estimation. However, this interval modelling leads to a very high number of expensive evaluations, which is not feasible for a high number of uncertain input parameters. To reduce the calculation time, surrogate models are used. Here, the full model is evaluated only at some grid points and the system response is approximated by mathematical approaches. Design and Analysis of Computer Experiments (DACE) offers a suitable surrogate model based on the Kriging method. The system model substituted in this way can be evaluated in an efficient way, but in addition to the uncertain simulation results, the approximation error dependent on the surrogate model has to be considered. Investigations of first prototypes lead to new knowledge that can be used to improve the surrogate model. Measurements, however, also include errors that are composed of systematic and random errors. The systematic measurement errors are specific errors for each measuring system and task, which are usually corrected during the measurement. However, an estimation of the random measurement error, which represents the precision of the measurement can be taken into account. Two methods are presented. Either an additional constant term is implemented in the standard Kriging or a superposition of two standard Kriging models, which are based on the simulation data and the measurement data, is used. As an application example a cold forging process of a steel gearwheel is employe
Keywords: Kriging; Measuring Data; Measuring Uncertainty; Surrogate Modeling

Teilprojekt 3: Metrologie und Messdatenverarbeitung für die geometrische Produktverifikation im Rahmen eines ganzheitlichen Toleranzmanagements. - Müller, Andreas; Binder, Felix; Hausotte, Tino (Abschlussbericht DFG-Forschungsgruppe FOR 2271, 2. Phase.Prozessorientiertes Toleranzmanagement mit virtuellen Absicherungsmethoden, 2023)

Towards efficient application-dependent dimensional measurements with computed tomography: optimized reduction of measurement duration using continuous scan mode: experimental investigations - Orgeldinger, Christian; Wohlgemuth, Florian; Müller, Andreas; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2022)
Due to the complex physical and technical relationships in dimensional X-ray computed tomography measurement technology, the precise influences on the measurement result are still not fully understood. A deeper understanding of these influences is essential in order to improve the measurement accuracy and economy of computed tomographic measurement systems. In addition, this enables better numerical determination of measurement uncertainties, which is also a topic of current research. Two factors that have a significant influence on the lead times are the scan mode and the number of projections per measurement. In this article, these factors are investigated experimentally using a calibrated workpiece, and the influence of the workpiece position on the measurement result is also examined. It can be shown that the workpiece position has a considerable influence on the quality of the measurement, especially in the case of a continuous scan. The results show a vast potential for application-dependent reduction of lead time

Transferring measured X-ray focal spots to virtual CT systems for more realistic simulations of dimensional measurements - Reuter, Tamara; Dittrich, Verena; Müller, Andreas; Hausotte, Tino (13th Conference on Industrial Computed Tomography (iCT) 2024, 2024)

Utilization of single point uncertainties for geometry element regression analysis in dimensional X-ray computed tomography - Müller, Andreas; Hausotte, Tino (9th Conference on Industrial Computed Tomography, 2019)
The work outlined in this paper is examining ways to incorporate previously determined single point uncertainties of computed tomography (CT) measurements into a suitable regression analysis in order to evaluate standard geometry elements. The goal is to determine and reduce the measurement uncertainty for the specific parameters of a geometry element by using selective point rejections based on their single point uncertainty. Examinations show that the systematic error as well as the associated uncertainties can be reduced in certain scenarios compared to the statistical interpretations of repeated (simulated) measurements without considering the single point uncertainty. Nonetheless, these results still need to be verified for different data series and measurement setups.<br
Keywords: single point uncertainty; measurement uncertainty; regression analysis; Monte Carlo simulation

Verbesserung dimensioneller Messungen auf Grundlage der Einzelpunktgüte und -Messunsicherheit - Müller, Andreas; Hausotte, Tino (VDI-Berichte Nr. 2365, 2019)
Zu einem Messergebnis als Näherungswert für den wahren Wert einer Messgröße soll immer die Angabe einer Messunsicherheit gehören. Diese grenzt nach der Korrektur der bekannten systematischen Messabweichungen einen Wertebereich ein, innerhalb dessen der wahre Wert der Messgröße mit einer anzugebenden Wahrscheinlichkeit liegt (üblich sind Erweiterungsfak-toren für gaußverteilte Messwerte k = 1 für ca. 68 %, bzw. k = 2 für ca. 95 %). Dieser Artikel soll zeigen, dass die punktweise Bestimmung und Angabe der Messunsicherheit für einzelne Bereiche einer vollständig erfassten Bauteiloberfläche anstatt für einzelne Messgrößen in vie-len Szenarien nutzbare Potenziale bzgl. der Verbesserung dimensioneller Messungen auf-weist. Zusätzlich sollen Anwendungsszenarien von lokalen Güteparametern für die industrielle Röntgen-Computertomografie zur Klassifizierung von Messartefakten und Abschätzung der lokalen Qualität der Messung vorgestellt werde
CRIS-Team Scopus Importer:2024-12-16
Keywords: Messunsicherheit; Einzelpunktgüte; Einzelpunktmessunsicherheit